TINJAUAN HUKUM ISLAM TERHADAP ADAT “RANDA SAHE KALEI BONGI” DALAM PERKAWINAN MASYARAKAT POTA KABUPATEN MANGGARAI TIMUR NUSA TENGGARA TIMUR - Hikmah Hariyati (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2022)
Abstract The custom that is often encountered is about marriage customs in Indonesia. One of them is the custom of marriage in the Pota community of East Nusa Tenggara. The custom of the Pota people in the wedding procession requires paying an Islamic dowry which the man must prepare but also a customary dowry which is usually known as the Randa Sahe Kalei Bongi custom. Customary traditions in marriage can be carried out provided that there is no conflict in the texts of the Qur'an or Islamic law. The traditional tradition of Randa Sahe Kalei Bongi can be associated with walimatul 'ursy. The purpose of the implementation of the Randa Sahe Kalei Bongi custom is to maintain the relationship between the bride's and the groom's extended family and to keep the kinship ties well-established. It can be said that the traditional practice of Randa Sahe Kalei Bongi also proves that how much the groom respects and gives love and affection to the bride and groom by agreeing to the traditional practice of Randa Sahe kalei bongi. The Randa Sahe Kalei Bongi custom can be made into law and does not conflict with Islamic Shari'a because this custom can be associated with walimah al-ursy. In relation to Randa Sahe Kalei Bongi, one of the objectives of the implementation is to hold a wedding party, so when viewed from the point of view of the purpose of its implementation, it can be equated in the process of walimah al-ursy. The Prophet also recommended "do walimah even if only with a goat".Keywords: Mahar, Randa Sahe Kalei Bongi Custom.